Rural Chinese Women’s Recognition of Intimate Partner Violence and their Potential Coping Strategies: A Qualitative Study - Hou, Fengsu (Journal of family violence, 2022)
Women are often the victims of intimate partner violence (IPV). Though China has established its first statute against domestic violence, there were limited studies related to IPV and only few focused on women’s perspectives of IPV. This study aimed to explore how women recognize and cope with IPV. This study completed the Short Explanatory Model Interview (SEMI) among a subset sample from a large epidemiology study in rural Sichuan China. After open coding, axial coding, and selective coding, we applied brief content analysis method to analyze qualitative interviews. Among 339 participants, the average age was 46.01 ± 12.42 years old and there were 49.26% of them had experienced violence from their partners in the last year. There were only 18 participants could recognize IPV; and there were 160 participants denied the violent relationship while blaming the victim for mental problems, serving a terrible role of wife, and less educated. One hundred and fifty-seven participants suggested solving IPV by oneself including fixing the relationship, empowering herself, enduring, doing housework, and even committing suicide; and 92 participants suggested seeking help from others including government agencies, her parents, friends, doctors, and legal aids. The results indicated that when women attributed the blame for IPV to the victim which may limit their coping strategies for self-help, and should they find themselves victimized. We believe future interventions should consider culture barriers and help vulnerable women define and perceive IPV in their lives, build broader social networks, and help victims dispel self-blame.